Radiation dose reports and determinants of image quality during ECG-triggered Cardiac Computed Tomography Angiography in children (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the radiation doses and determinants of image quality during prospective and retrospective ECG-triggered cardiac computed tomography angiography.Materials and Methods: Patients included study who underwent ECG-triggered and low radiation dose dual-source cardiac computed tomography angiography scans. Dose length product values were obtained from the computed tomography scanning protocol. Effective dose (mSv) was estimated using the dose length product method with a conversion factor (mSv/mGy × cm). All images were evaluated and scored by two pediatric radiologists. Results: 37 patients have ECG-triggered cardiac computed tomography. The ages of the patients were between 3 days to 17 years (mean 73.78 ±79.95 months). The average heart rate of the patients was 101.11±27.12 bpm. The mean DLP was 93.05 ±64.4 mGy/cm. The mean effective dose was calculated as 1.74 ±1.03 mSv. We found good agreement between observers while analyzing determinants of image quality (kappa values 0.71-0.80).Conclusion: High-quality images with a low dose can be obtained with an ECG-triggered cardiac computed tomography angiography method. Because of the high sensitivity of radiation in children, dose reduction techniques should be used effectively. Cardiac computed tomography examinations can be performed at diagnostic quality limits with prospective ECG-triggered technique in patients with high pitch, low kV, and dual source techniques.
Keywords: Cardiac computed tomography angiography; children; radiation dose